THE MAKING OF EDUCATIONAL GAME AS A LEARNING MEDIA - Paskalis Limur; Siti Supeni; Yudhistiro Pandu Widhoyoko (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
The purpose of this study is how the procedure for making learning media using Smart AppsCreator. This is done to make children interested in learning so that it has implications forincreased learning outcomes. The method of the research is Research and development usingprocedures as follows Analysis, Design, Development and Evaluation.The results of this study are first, making learning media is used by adjusting the ADDIEprocedure. Second, the learning media product is said to be interesting and feasible to use asshown by the validation results from the material expert in the Very Eligible category with ascore of 5. A score of 4 is categorized as Eligible. Entered in the Not Too qualification with ascore of 3. Infeasible category with a score of 2. And Very Inappropriate category with a scoreof 1.Keywords: Smart Apps Creator, Learning Media, Educational game